2021
DOI: 10.1038/s41598-021-91927-4
|View full text |Cite
|
Sign up to set email alerts
|

Abyssal deposit feeders are secondary consumers of detritus and rely on nutrition derived from microbial communities in their guts

Abstract: Trophic ecology of detrital-based food webs is still poorly understood. Abyssal plains depend entirely on detritus and are among the most understudied ecosystems, with deposit feeders dominating megafaunal communities. We used compound-specific stable isotope ratios of amino acids (CSIA-AA) to estimate the trophic position of three abundant species of deposit feeders collected from the abyssal plain of the Northeast Pacific (Station M; ~ 4000 m depth), and compared it to the trophic position of their gut conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
1
6
1
1
Order By: Relevance
“…Durden et al (2020) found that deposit-feeding megafauna (e.g., echinoids, large holothurians, and asteroids) did not alter their deposit feeding strategy in relation to the seasonality in detrital supply (i.e., changes in the amount of nutrients that reach the seafloor). Also, the guts of abyssal deposit feeders (e.g., E. rostrata) have recently been established as hotspots of organic matter that occupy one trophic level above detritus (Romero-Romero et al, 2021). Our results showed no positive correlation between POC fluxes and FD values.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Durden et al (2020) found that deposit-feeding megafauna (e.g., echinoids, large holothurians, and asteroids) did not alter their deposit feeding strategy in relation to the seasonality in detrital supply (i.e., changes in the amount of nutrients that reach the seafloor). Also, the guts of abyssal deposit feeders (e.g., E. rostrata) have recently been established as hotspots of organic matter that occupy one trophic level above detritus (Romero-Romero et al, 2021). Our results showed no positive correlation between POC fluxes and FD values.…”
Section: Discussioncontrasting
confidence: 68%
“…Our results seem to corroborate that parameters other than high or low prior POC fluxes control E. rostrata foraging movements. Thus, considering previous studies (e.g., Kaufmann and Smith, 1997;Vardaro et al, 2009;Koy and Plotnick, 2010;Durden et al, 2020;Romero-Romero et al, 2021), the obtained data, and that the nutrient content is not related to E. rostrata path complexity, phytodetritus distribution may be the dominant cause of echinoid movement. Analysis of environments with different levels of patch quality and variable travel times between patches must be conducted to resolve these uncertainties and attempt to more generally apply optimal foraging theory to deep-sea echinoids.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that δ 13 C fractionates less than 1.0‰ for each trophic position. The Δ 13 C between the mean water column POM-δ 13 C (-24.13 ± 1.56‰) and fish/crustaceans δ 13 C (-18.10 ± 0.93‰) of the SEMS amounted to 6.04‰ (equal to at least six trophic positions), and therefore, cannot be attributed to trophic enrichment alone, but could be partly linked to the regeneration of benthic carbon sources, which may be relevant for detritus feeding animals, including all of the crustacean and some of the fish studied here Moreover, our δ 13 C-C/N data support the potential effect of microbially degraded phyto-detritus resulting in higher isotopic values of nitrogen and carbon in deep benthic food webs compared with pelagic food webs (Papiol et al, 2013;Romero-Romero et al, 2021).…”
Section: Discussionsupporting
confidence: 51%
“…From a certain inter‐trophic enrichment between consumer detritivores and dead OM, AA‐SIR can assess and quantitatively estimate the role of detritus complex as food web component. For instance, abyssal detritivores (Riekenberg et al, 2021 ; Romero‐Romero et al, 2021 ) and micro‐/mesozooplanktons (Doherty et al, 2021 ) showed higher AA δ 15 N composition and higher TP relative to nutritional resources as derived from detrital OM (i.e., zooplankton fecal pellet). Furthermore, it is available to examine the trophic connections between the brown food chains and the green food chains.…”
Section: Interpretation Of Aa‐sir For Defining Trophic Transfer Betwe...mentioning
confidence: 99%